الأدوار الاجتماعية للزوايا العلمية بالجنوب الغربي للجزائر خلال المرحلة الاستعمارية - شنتير, نجاة; شترة, خيرالدين (جامعة الوادي - University of Eloued, 2022)
تتناول هذه الدراسة موضوع الزوايا العلمية بالجنوب الغربي للجزائر خلال المرحلة الاستعمارية وكيف كانت هذه الزوايا بمثابة الحصن الحصين للأمة والمجتمع، في محافظتها على سلامة العقيدة الإسلامية والمبادئ الوطنية الصحيحة، وكيف صانت القيم الإنسانية ورسَّخت مكارم الأخلاق، وكيف ساهمت في نشر ثقافة التعاون الاجتماعي، وكرست مبادئ التآلف المجتمعي، فكانت المأوى الآمن لعابري السبيل، والسند الوفي للفقراء والمساكين والمحتاجين، والقلعة الحصينة لمقومات المجتمع من عادات وتقاليد وأعراف. وهذا بحثاً عن جملة إجابات تتعلق ببعض الأسئلة الجوهرية في هذا الموضوع، ومنها: كيف نشأت وتطورت الزوايا في مجتمع الصحراء الجزائرية؟ ما هي الزوايا الرائدة للحركة العلمية والثقافية بإقليم الجنوب الغربي للجزائر خلال القرنين (11هـ/12ه)و(17م/18م)، ثم ما هي الأدوار الدينية والتربوية لهذه الزوايا؟ وما مظاهر نشاطها الاجتماعي؟ وكيف ساهمت الزوايا العلمية في تنشيط المجالات الاجتماعية والثقافية خلال فترة الركود والسكونية التي ضربت بنية المجتمع الجزائري عموماً، وساكنة الأقاليم الثلاثة للجنوب الغربي خلال المرحلة الاستعمارية؟. This study tackles the topic of the Scientific Institutions of the SouthWest of Algeria during the colonial phase. By means of discussing how these Institutions served as the fortress of the nation and society in maintaining the integrity of the Islamic Faith and the right national principles. How it safeguarded the human values and entrenched the ethical values. How it contributed to the dissemination of the culture of the social cooperation, also it enshrined the principles of the societal harmony. As it was the safe shelter for the passers-by, the loyal support for the poor, the destitute and the needy, and the fortified fortress of the society's constituent customs, traditions and mores. This research is about a set of answers concerning some of the substantive questions on this topic, including: How the Institutions originated and evolved in the society of the Algerian desert? What are the leading institutions of the scientific and cultural movement in Algeria's South-Western region during the two centuries (11 AH / 12 AH) and (17 AD / 18 AD), Then what are the religious and educational roles of these Institutions? What are the aspects of its social activity? How it embodies its cultural role of a social dimension? How much have the region's scientists contributed to revitalizing social and cultural life? How did the Scientific Institutions contribute to the revitalization of social and cultural spheres during the period of stagnation and dormancy that struck the structure of the Algerian society in general, and of the three territories of the South-West during the colonial phase?
مقال
Keywords: الزوايا العلمية – الطرق الصوفية- تاريخ الجزائر- الجنوب الغربي للجزائر- الاستعمار الفرنسي; The Scientific Institutions – the Sufi Paths – the history of Algeria – the Algeria's South-West - the French Colonization